Efektivitas Pengawasan Penerapan Prinsip Syariah Oleh Dewan Pengawas Syariah (DPS) (Studi Kasus Pada PT. BPRS Amanah Sejahtera) - Devika Refgiani; Suherman Rosyidi (Jurnal Ekonomi Syariah Teori dan Terapan, 2016)
This research using qualitative approach while research method used was a case study with using pattern matching technique for analyzing. The analysis is done by looking at the suitability of supervision of the implementation of sharia principle by DPS on BPRS Amanah Sejahtera with SEBI No 15/22/DPbS. The results can be concluded that monitoring of product and new activity by DPS on BPRS Amanah Sejahtera had been in accordance with SEBI N0 15/22/DPbS. The supervision toward activity for raising funds, financing and other services activities by DPS on BPRS Amanah Sejahtera does not satisfy one of the nine points contained in the SEBI No 15/22/DPbS. In general, the supervision by DPS on BPRS Amanah Sejahtera has been effective because DPS not only doing the good supervision but also make improvements and development, DPS monitoring with his best, and DPS give priority to the BPRS Amanah Sejahtera.